Self-reported eating habits and dyslipidemia in men aged 20-39 years: the Japan Environment and Children's Study - Meishan Cui; Satoyo Ikehara; Kimiko Ueda; Kazumasa Yamagishi; Hiroyasu Iso; the Japan Environment and Children's Study Group (Komiyama Printing Co. Ltd, 2023)
Background and aims: Unhealthy eating behaviors, including eating fast, eating after satiety, skipping breakfast, and eating out are common among men aged 20-39 years. In this cross-sectional study, we aimed to examine the association between self-reported eating habits and the prevalence of dyslipidemia. Methods: The participants of this study were 38,233 men aged 20-39 years, whose food consumption frequency related information was collected through a questionnaire. Dyslipidemia was defined as total cholesterol (TC) ≥190 mg/dL, fasting triglyceride (TG) ≥150 mg/dL and non-fasting TG ≥175 mg/dL, high-density lipoprotein cholesterol (HDL-C) <40 mg/dL, low-density lipoprotein cholesterol (LDL-C) ≥140 mg/dL. Odds ratios (ORs) and 95% confidence intervals were calculated relative to healthy eating habits using logistic regression, after adjustment for age, study unit, and other potential confounding factors. Results: Moderate and fast speeds were associated with a higher prevalence of reduced HDL-C (by 27% and 26%, respectively) compared to slow speeds. Eating after satiety was associated with a higher prevalence of elevated TC (by 16%) and elevated TG (by 11%), elevated LDL-C (by 21%). Breakfast eating of 1-4 times/week and <1 time/week were associated with a higher prevalence of elevated TC (by 11% and 16%, respectively) and elevated LDL-C (by 21% and 38%, respectively) compared to that of ≥5 times/week. Eating out of ≥5 times/week was associated with a 13% higher prevalence of elevated TG. Conclusions: All of four unhealthy eating habits were associated with a higher prevalence of dyslipidemia in men aged 20-39 years.